Green Computing - K. Shalini; K. Naga Prasanthi (Universitas Islam Sultan Agung, 2013)
Green computing is all about using computers in a smarter and eco-friendly way. It is the environmentally responsible use of computers and related resources which includes the implementation of energy-efficient central processing units, servers and peripherals as well as reduced resource consumption and proper disposal of electronic waste .Computers certainly make up a large part of many people lives and traditionally are extremely damaging to the environment. Manufacturers of computer and its parts have been espousing the green cause to help protect environment from computers and electronic waste in any way.Research continues into key areas such as making the use of computers as energy-efficient as Possible, and designing algorithms and systems for efficiency-related computer technologies.